2003
DOI: 10.4040/jkan.2003.33.8.1171
|View full text |Cite
|
Sign up to set email alerts
|

Decisional Balances and the Process of Change in Smoking Cessation in Patients with Coronary Artery Diseases

Abstract: Purpose. Despite many smoking cessation programs, many patients with CAD continue to smoke or re-smoke.The processes of change and self-change for smoking cessation is emphasized. The purpose of present study was to investigate decisional balances and processes of change according to stages of change for smoking cessation in the patients with CAD.Methods. This descriptive study was performed using the self-reported questionnaires from 157 male patients with CAD who have smoking experiences. The questionnaires … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Second, among social support, an interpersonal aspect, family support showed a positive correlation with smoking cessation. In a study conducted on smokers with coronary artery disease in Korea, family support was reported as a signifcant factor infuencing the intention and practice of smoking cessation [29]. Family support is a crucial factor in the successful aging of Korean older adults [30], and it was shown as an important variable in smoking cessation practice.…”
Section: Discussionmentioning
confidence: 99%
“…Second, among social support, an interpersonal aspect, family support showed a positive correlation with smoking cessation. In a study conducted on smokers with coronary artery disease in Korea, family support was reported as a signifcant factor infuencing the intention and practice of smoking cessation [29]. Family support is a crucial factor in the successful aging of Korean older adults [30], and it was shown as an important variable in smoking cessation practice.…”
Section: Discussionmentioning
confidence: 99%